Accounting for climate policies in Europe's sovereign debt market - Marta Domínguez-Jiménez; Alexander Lehmann (Bruegel, 2021)
International debt investors increasingly demand assets that are aligned with environmental, social and governance objectives. Sovereign debt is being belatedly swept up in this change. This huge asset class represents a uniquely long-term claim and funds a wide range of public expenditure, both brown and green. Public capital expenditures will be a central part of the roughly exteuro3 trillion investment budget needed to pay for the European Green Deal. European Union countries have so far met investor appetite for climate-aligned assets through sovereign green bonds, the issuance of which has rapidly grown since 2017. The EU itself will also issue green bonds in large volumes. However, because of some inherent flaws in such instruments and as their still-weak frameworks, these bonds are unlikely to meet the environmental criteria demanded by investors, and will complicate established principles in sovereign debt management. Much more comprehensive information is needed on the climate related aspects of the public budgets of EU countries. Greater transparency in this respect would support stability and improve the functioning of capital markets, given that sovereign debt plays a pivotal role in all investor portfolios and also in regulatory and monetary policy. Adoption by sovereign issuers of green budgeting principles, based on a common taxonomy of sustainable activities, would enhance transparency. It could also be driven by investors who, under new EU rules, must disclose the climate-related aspects of all financial instruments offered in the capital market.
Keywords: 330